Habitar e viver: aspectos culturais de uma casa bioconstruída e de uma Ecovila na região da grande Goiânia - Oliveira, Guilherme Monteiro (2020)
The various crises that have occurred in Brazil and in the world in recent decades have led to several questions about our actions and the impact they have on the environment. The article aims to analyze how the global phenomenon of Permaculture and bioarchitecture are related to this emerging criticism of the construction patterns of the house and the way of living. With ethnography, more specifically ethnobiography, I was able, in my research, to approach characters and obtain reflective and subjective data in order to understand the context in which they are inserted and to understand how their ways of indwelling and living are related to their life stories . The house, more than a space to protect itself from the weather, is a space full of history, symbols and meanings and through participant observation, camera in hand and semi-structured interviews, it was possible to conclude that there is a cultural dimension in the bioconstructed house and in the ecovillage, since the inhabited space is directly related to the worldviews of those who live there, in addition to communicating the values of its residents